Skrifbeskouing en oorredingsretoriek: perspektiewe op performatiewe prediking - Johan Cilliers (Acta Theologica)
This article starts out by giving a brief summary of the typical Reformed understanding of the performative (sacramental) character of Scripture and the implications thereof for preaching. The critique that has been levelled against this understanding of Scripture and preaching, initiated through the mind-set of the Enlightenment (Kant), gaining momentum since the Second World War, and coming to full fruition in the so-called postmodernism, is briefly addressed. The article closes with suggestions concerning the rhetorical strategies of persuasion found in Scripture, and how this may enable preachers to still attain preaching that is “performative”.